Stability of Lactobacillus rhamnosus GG incorporated in edible films: Impact of anionic biopolymers and whey protein concentrate. (September 2017) - Soukoulis, Christos; Behboudi-Jobbehdar, Solmaz; Macnaughtan, William; Parmenter, Christopher; Fisk, Ian D.
Abstract: The incorporation of probiotics and bioactive compounds, via plasticised thin-layered hydrocolloids, within food products has recently shown potential to functionalise and improve the health credentials of processed food. In this study, choice of polymer and the inclusion of whey protein isolate was evaluated for their ability to stabalise live probiotic organisms. Edible films based on low (LSA) and high (HSA) viscosity sodium alginate, low esterified amidated pectin (PEC), kappa-carrageenan/locust bean gum (κ-CAR/LBG) and gelatine (GEL) in the presence or absence of whey protein concentrate (WPC) were shown to be feasible carriers for the delivery of L. rhamnosus GG. Losses of L. rhamnosus GG throughout the drying process ranged from 0.87 to 3.06 log CFU/g for the systems without WPC, losses were significantly reduced to 0 to 1.17 log CFU/g in the presence of WPC. Storage stability (over 25d) of L. rhamnosus GG at both tested temperatures (4 and 25 °C), in descending order, was κ-CAR/LBG > HSA > GEL > LSA = PEC. In addition, supplementation of film forming agents with WPC led to a 1.8- to 6.5-fold increase in shelf-life at 4 °C (calculated on the WHO/FAO minimum requirements of 6 logCFU/g), and 1.6–4.3-fold increase at 25 °C. Furthermore probiotic films based on HSA/WPC and κ-CAR/LBG/WPC blends had both acceptable mechanical and barrier properties. Graphical abstract: L. rhamnosus GG survival in edible films – the interrelation between the physical and optical film properties and L. rhamnosus GG survival during storage. Highlights: Whey protein concentrate (WPC) inclusion enhanced survival during drying and storage. WPC inclusion reduced water vapour permeability and Tg. Cell viability was greatest in pectin/WPC films during drying. Cell viability was greatest in composite carrageenan/locust bean gum/WPC films during storage.